2002
DOI: 10.1074/jbc.m201267200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Non-conventional Heat Shock Element Regulates Expression of MDJ1 Encoding a DnaJ Homolog in Saccharomyces cerevisiae

Abstract: The heat shock factor (HSF) is a pivotal transcriptional factor that regulates the expression of genes encoding heat shock proteins (HSPs) via heat shock elements (HSEs). nGAAnnTTCnnGAAn functions as the minimum consensus HSE (cHSE) in vivo. Here we show that the expression of Saccharomyces cerevisiae MDJ1 encoding a mitochondrial DnaJ homolog is regulated by HSF via a novel non-consensus HSE (ncHSE MDJ1 ), which consists of three separated pentameric nGAAn motifs, nTTCn-(11 bp)-nGAAn-(5 bp)-nGAAn. This is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 79 publications
0
24
0
Order By: Relevance
“…We have further analyzed the 5Ј-flanking regions of genes lacking the known types of HSE and identified a novel HSE consisting of three nTTCn direct repeats separated by 5-bp blocks. Some of the previously identified Hsf1 targets, such as HSP60, HSC82, UBI4, EDC2, and RPN4 (37,42,(47)(48)(49), were not recognized as Hsf1-regulated genes in the present work. The number of Hsf1-regulated genes identified was smaller than the number of Hsf1-bound genes, the latter being ϳ165 (20).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…We have further analyzed the 5Ј-flanking regions of genes lacking the known types of HSE and identified a novel HSE consisting of three nTTCn direct repeats separated by 5-bp blocks. Some of the previously identified Hsf1 targets, such as HSP60, HSC82, UBI4, EDC2, and RPN4 (37,42,(47)(48)(49), were not recognized as Hsf1-regulated genes in the present work. The number of Hsf1-regulated genes identified was smaller than the number of Hsf1-bound genes, the latter being ϳ165 (20).…”
Section: Discussionmentioning
confidence: 50%
“…The notable enrichment of the sequence in the Hsf1-regulated genes (20%, 12 of 59 genes), relative to the entire genome, supports the functional role as the HSE. It was previously reported that MDJ1 and YDJ1 (containing the step-type HSE) have a non-conventional HSE comprising nTTCn(11 bp)nGAAn(5 bp)nGAAn (47). We suggest that interaction with the two sequences leads to cooperative binding of the Hsf1 trimers.…”
Section: Discussionmentioning
confidence: 94%
“…In the PNC1 promoter, the heat shock response requires not only the directly repeated units but also several units that are located in varying positions. An exceptional HSE was also found in the MDJ1 promoter, in which the third nGAAn unit is far away from the two regularly arranged units (15). It was shown that a pair of direct repeats is not sufficient to function as the HSE (15,20).…”
Section: Discussionmentioning
confidence: 94%
“…An exceptional HSE was also found in the MDJ1 promoter, in which the third nGAAn unit is far away from the two regularly arranged units (15). It was shown that a pair of direct repeats is not sufficient to function as the HSE (15,20). Thus, although the presence of a regularly positioned third unit is needed for the binding of ScHsf1, functional HSEs tolerate slightly divergent configurations.…”
Section: Discussionmentioning
confidence: 95%
“…While the role of the highly conserved HSE in directing HSF binding to specific loci has been well established in yeasts and metazoans (33,51,52), a number of studies have demonstrated that there are distinct types of HSEs bound by S. cerevisiae HSF, as well as distinct HSEs that are preferentially bound by the HSF1 and HSF2 isoforms in mammals (1). Indeed, the cooperative binding of S. cerevisiae HSF to multiple nonconsensus HSEs may be enhanced by heat shock or other stresses (10,13,45). To attempt to understand the determinants that govern the heat shock-dependent binding distribution of HSF within the S. cerevisiae genome, we applied the pattern-finding program MDscan (29) to distinct subsets of the HSF target loci identified here by ChIP-DNA microarray experiments.…”
mentioning
confidence: 99%